Prenatal whole-exome sequencing for fetal structural anomalies: a retrospective analysis of 145 Chinese cases - Yayun Qin; Yanyi Yao; Nian Liu; Bo Wang; Lijun Liu; Hui Li; Tangxinzi Gao; Runhong Xu; Xiaoyan Wang; Fanglian Zhang; Jieping Song (BMC, 2023)
Abstract Background Whole-exome sequencing (WES) significantly improves the diagnosis of the etiology of fetal structural anomalies. This study aims to evaluate the diagnostic value of prenatal WES and to investigate the pathogenic variants in structurally abnormal fetuses. Methods We recruited 144 fetuses with structural anomalies between 14 and 2020 and 15 December 2021 in the study. Genetic screening was performed by WES combined with karyotyping and chromosomal microarray analysis. The molecular diagnostic yield of prenatal WES for each type of fetal structural anomaly and the identified pathogenic genes and mutations were reported. Results In this study, we retrospectively analyzed the clinical and genetic data of 145 structurally anomalous fetuses. These cases were classified into 9 phenotypic classes based on antenatal ultrasound findings. Thirty-eight pathogenic variants in 24 genes were identified in 35 of the 145 cases, including 14 novel variants in 13 genes (EP300, MYH3, TSC2, MMP9, CPLANE1, INVS, COL1A1, EYA1, TTC21B, MKS1, COL11A2, PDHA1 and L1CAM). Five additional pathogenic variants were classified as incidental findings. Our study showed that the overall diagnosis rate of WES was 28.1% (27/96) in the parent-fetus trio cases and 16.3% (8/49) in the proband-only cases. Fetuses with musculoskeletal anomalies had the highest diagnostic yield (51.4%, 19/37). In addition, FGFR3 and COL1A1 were the most common pathogenic genes. Conclusions Our work expands the mutation spectrum of the genes associated with fetal structural anomalies and provides valuable information for future parental genetic counselling and pregnancy management of the structurally anomalous fetuses.